HETEROCHROMATIN AND KARYOTYPE REORGANIZATION IN FISH OF THE FAMILY ANOSTOMIDAE (CHARACIFORMES) - Galetti, P. M.; Mestriner, C. A.; Venere, P. C.; Foresti, F. (Karger, 1991)
Mitotic chromosomes of four fish species of the family Anostomidae, belonging to the genera Leporinus, Leporellus, and Schizodon, were studied. With 2n = 54 meta- and submetacentric chromosomes, this family appears to be characterized by marked karyotypic stability. Although perceptible differences exist, mainly in the amount of constitutive heterochromatin present in the chromosomes of these species, these differences do not affect the structure and/or size of these chromosomes. Chromatin substitutions and/or modifications may have led, in one direction, to an increase in heterochromatin in some species and, in the opposite direction, to heterochromatin reduction in others. Whether these changes are accompanied by changes in the amount of euchromatin in the chromosomes is an open question. The nucleolar organizer regions, which may be located on different chromosomes in the various species, may also be indicators of reorganization of these karyotypes.